The ndongo bowl lyre of the Baganda: an examination of its sonic properties - Makubuya, James (International Library of African Music, 1999)
The term ndongo refers to the eight-string bowl lyre of the Baganda, a people that live in the south central region of the landlocked East African nation of Uganda (see Fig. 1). In the musical tradition of the Baganda, the ndongo is one of their oldest string musical instruments, second only to the ennanga 8- string arched harp. Owing to the natural passing away of the people who knew how to play it, the steady decline in use of the ennanga as a folk instrument has been noticed. Instead, the ndongo has gradually replaced it; and today it is very widely played during many cultural and social functions throughout the entire kingdom of Buganda.
Keywords: African Music